Building Community. The Performing Arts in European Cultural Policies - Massimo, Serena (Aesthetica Preprint, 2023)
Although the term “performativity” does not appear in European cultural policies documents, the identification of culture as a “transformative force for community regeneration” and the strategies outlined to promote a strong sense of community with economic and sustainable growth certainly do appear to rely to a significant degree upon the performative potential of culture and art. The use of the notion of performativity as a tool for interpreting those policies enables us to put in light certain theoretical points whose lack of explicit expression generates contradictions and ambiguities, and helps us to see how the recognition and the valorisation of the performative potential of culture and art facilitate the attainment of the goals set by those policies.